A View of Managership and Leadership from 30,000 Feet: An Historical Perspective - Muczyk, Jan; Adler, Terry (Journal of Comparative International Management)

(untitled) (Management Futures, 2018)
To the extent that there is considerable ambiguity and overlap when it comes to defining the managership and leadership constructs and their components, progress in advancing the field has appreciably slowed; but the frustration of scholars and practitioners is not abated. Hence, what is needed is a good faith effort to take a look at these constructs from 30,000 feet in order to get a better view of the ambiguities and overlaps which are harder to detect from the ground level. Such an effort invariably requires an historical perspective. Precise definitions of management and leadership constructs are necessary so that researchers possess adequate constructs required for formulating testable hypotheses. Moreover, international and American scholars need to be on the same page. Until that is accomplished, progress in advancing the field will continue to be stymied. Toward that end, this effort attempts to identify the ambiguities and overlaps and proposes tentative solutions.